2015
DOI: 10.1080/00036846.2015.1117046
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the dynamic relationship between international and China’s crude oil prices

Abstract: This article studies the dynamic relationship between international (WTI, Brent and Dubai) and domestic (Da Qing) crude oil prices in China using threshold cointegration method. We find evidence of a long-run equilibrium relationship between each pair of international and Da Qing oil prices, favouring the market integration hypothesis. We also estimate asymmetric adjustments under the momentum threshold autoregressive (M-TAR) specification in a TVECM, and the results show that adjustments to eliminate disequil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…As we found that the shocks from the 2008 financial crisis and the COVID-19 on the relationships between the Chinese and international energy markets were driven by the effects on the Chinese fossil fuel market, the stakeholders in the Chinese fossil fuel market need to pay more attention to the Chinese fossil fuel market when considering the risk involved in trading between the Chinese and international energy markets. As argued by Chan and Woo (2016), China should consider its domestic fossil fuel market when examining the dynamic relationship between the Chinese and international energy markets suggesting that policymakers should account not only for the dynamics relationships but also attach importance to the dynamic relationship driven by the Chinese fossil fuel market when stabilizing energy prices during the crises.…”
Section: Discussionmentioning
confidence: 99%
“…As we found that the shocks from the 2008 financial crisis and the COVID-19 on the relationships between the Chinese and international energy markets were driven by the effects on the Chinese fossil fuel market, the stakeholders in the Chinese fossil fuel market need to pay more attention to the Chinese fossil fuel market when considering the risk involved in trading between the Chinese and international energy markets. As argued by Chan and Woo (2016), China should consider its domestic fossil fuel market when examining the dynamic relationship between the Chinese and international energy markets suggesting that policymakers should account not only for the dynamics relationships but also attach importance to the dynamic relationship driven by the Chinese fossil fuel market when stabilizing energy prices during the crises.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the study on the integration of the world crude oil market, some scholars [11][12][13] have also involved the Chinese market to better reflect the overall changes of the world crude oil market. Specifically, Li and Leung [14] and Chan et al [15] explore the influence of China's oil market on the world oil market by introducing Daqing crude oil spot. All these studies show that China has become a member of the "Great Pool".…”
Section: The Lead-lag Relationship Among Different Oil Marketsmentioning
confidence: 99%
“…Yin and Xiyuan (2020) analyze the correlation of stock markets and oil price volatility. Chan and Woo (2016) explore the nexus between international and Chinese oil prices. Zhu et al (2019) analyze the relation between international oil prices and Chinese commodity futures markets, using quantile regression.…”
Section: Theoretical Analysis Data and Estimationmentioning
confidence: 99%